Effect of Zinc Supplementation in Acute Watery Diarrhea in Children 6 Months to 5 Years - Khan, Sahrish; Khalid, Komal; Zahid, Masroor; Ali, Armaghan (Biological and Clinical Sciences Research Journal, 2025)
AWD is the third most common cause of childhood morbidity and mortality in the developing world today. Iron deficiency anemia, and more commonly zinc deficiency, remain rife, especially among children in these areas, thus exposing them to a weakened immune system. It was known from the report that Zinc is said to have been recommended by the World Health Organization (WHO) as a means to shorten the duration and lessen the severity of diarrhea. Objectives: to determine the role that zinc supplementation has on the duration, severity, and frequency of acute watery diarrhoea among children of 6 months to 5 years of age. A quasi-experimental study. Methods: The study was conducted in the Pediatric A ward, Ayub Medical Complex, Abbottabad in the duration from 27 September 2024 to 27 March 2025. A total of 150 children between 6 months and 5 years of age presented with acute watery diarrhea. The patients were divided into two groups: 75 accepted zinc supplementation (20 mg/day for 10 days) and 75 children received no additional zinc. More specifically, the number of diarrheal stools per day, as well as the total number of diarrheal stools and days, were obtained. The level of statistical significance was determined by p-value and standard deviation (SD). Results: out of 150 patients, prophylactic effect in children receiving zinc supplementation was experienced diarrhea for a shorter time in terms of the mean duration: 3.5±1.2 against 5.1±1.8 in the control group, p < 0.05. In the same way, the frequency of stools was lower in the zinc group compared to the placebo group. The zinc group had a standard deviation of 1.2 for the duration of diarrhea, and the control group had a standard deviation of 1.8, and the p-value = 0.01, which shows that our findings are significantly different. There were no clinically significant adverse effects in either study group. Conclusions: The present study shows that zinc supplementation clearly shortens the duration and mitigates the severity of acute watery diarrhea among children aged between 6 months to 5 years. This enhances the process of extending the traditional course of zinc support during diarrhea management to enhance course favorable results as well as minimize the load on the health care systems.